The Functions of Discourse Markers in Fairy Tale of Thumbelina by Hans Christian Andersen - Herman Herman; Juliana Sihombing; Nguyen Van Thao (Universitas Muhammadiyah Mataram, 2018)
The aim of this research is to investigate the use of discourse markers in written fairy tale. In order to achieve the aim of this research, the following objective is set to analyze the percentage and the functions of discourse markers in the fairy tale of Thumbelina. The approach to this research is qualitative as well as discourse analysis method was chosen for the analysis. After analyzing the data, the research found that total word count of the fairy tale of Thumbelina was 4,335, which was taken as the basis for calculating the frequency of each DM. Within 4,335 words 41 different DMs were identified, but the number of occurrences of each DM was quite different. Total number of all DMs occurrences was 415 which composed 10.44 % of the total word count. Taking into consideration functions of DMs, there were found 358 occurrences of DMs fulfilling textual functions and 57 occurrences of DMs in interpersonal functions. Based on the result, the percentage of occurrences of discourse markers are more frequent in the textual discourse markers (86, 3%) than interpersonal discourse markers (13, 7%).